Students' Reflective Thinking In Economic Learning - Devi Wulan Ashari; Fadhiya Ulhaq; Enceng Yana; Hermansyah Hermansyah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
The inability of students to grasp a concept or solve problems during the learning process is an inevitable occurrence. One such instance is when students encounter challenges in solving economic problems. Addressing the issue of students' inability to analyze questions in economics learning is essential, as every student inherently possesses the potential for analytical problem-solving abilities. This research is a qualitative research project involving high school students in Cirebon Regency as participants. The data collection techniques employed in this research include observation, data analysis, and in-depth interviews. The objective of this research is to investigate how students utilize their reflective thinking abilities in problem-solving within the context of economics learning. In this research, learning styles exert the greatest influence on economics learning in schools. Several factors contribute to students' reluctance to complete economics assignments, including differences in students' learning styles. Some students prefer theoretical learning, while others prefer practical learning. Additionally, obstacles arise from a lack of self-awareness, which hinders reflective thinking. In this research, learning styles emerge as the primary influencer on economics education within schools. Numerous factors contribute to students' reluctance to complete economics assignments, notably variances in their learning styles. While some students gravitate towards theoretical learning, others lean towards practical learning. Moreover, challenges arise from a deficiency in self-awareness, impeding reflective thinking.